Design measurement for food packaging design: a design development - RAJA, SUHAYLAH (PGSC USM, 2019)
Quantification on design has taken place in both the industrial and academic fields. It is empirical to understand the importance of design quantification in meeting the end–users’ preferences. The judgements of people with design sensitivity are relevant in providing an additional measurement approach for quantifying design and its’ visual appearance. To date, the importance of the primary display panel (PDP) of a food packaging design is an essential aspect to look at in providing visual information to cater new circular business models—particularly those focusing on Small Medium Enterprise of the micro food and beverage businesses. In addition, this development of design measurement might also be implemented within the emergence of sustainable design. Hence, in achieving the United Nation’s Sustainable Development Goals, this study will focus on the 9th goal to promote the industry, innovation and infrastructure through design development. As such, this paper aims to address this gap by analysing the significance of people with design sensitivity and their responsibility to shape the current way food packaging is designed using the two–dimensional approach. This measurement will be identified as the Centrality Visual Product Aesthetics (CVPA) in addition to the existing design strategies of food packaging design.